1994
DOI: 10.1038/hdy.1994.115
|View full text |Cite
|
Sign up to set email alerts
|

Causes and consequences of esterase 6 enzyme activity variation in pre-adult Drosophila melanogaster

Abstract: We report heritable threefold differences in both larval and pupal esterase 6 activity among 17 isoallelic lines of D. melanogasrer extracted from a natural population. The activity differences in the two stages are only weakly correlated with each other or with previously determined values for esterase 6 activity in adults of these lines. The pre-adult activity variation is also unrelated to polymorphisms among the lines for six esterase 6 allozymes and six restriction sites in a region encompassing the ester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The role of Est-6 in D. melanogaster mating propensity (Richmond et al, 1980(Richmond et al, , 1990Ludwig et al, 1993); its association with increased reproductive fitness, pre-adult viability, tissue expression pattern, and levels of enzyme activity strongly indicate that natural selection is involved in shaping the S/F and Rsa I 2 / Rsa I þ polymorphisms (Gromko et al, 1984;Game and Oakeshott, 1990;Richmond et al, 1990;Ludwig et al, 1993;Oakeshott et al, 1994Oakeshott et al, , 1995Odgers et al, 1995;Tamarina et al, 1997). Our window analysis also supports that these are balanced polymorphisms (Fig.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The role of Est-6 in D. melanogaster mating propensity (Richmond et al, 1980(Richmond et al, , 1990Ludwig et al, 1993); its association with increased reproductive fitness, pre-adult viability, tissue expression pattern, and levels of enzyme activity strongly indicate that natural selection is involved in shaping the S/F and Rsa I 2 / Rsa I þ polymorphisms (Gromko et al, 1984;Game and Oakeshott, 1990;Richmond et al, 1990;Ludwig et al, 1993;Oakeshott et al, 1994Oakeshott et al, , 1995Odgers et al, 1995;Tamarina et al, 1997). Our window analysis also supports that these are balanced polymorphisms (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Game and Oakeshott (1990) found that a polymorphism at an Rsa I site in the 5 0 -flanking region of Est-6 shows significant association with the amount and activity of EST-6 in males. Given the evidence from other studies that differences in male EST-6 activity affect the reproductive success of their mates (Richmond et al, 1990), Game and Oakeshott (1990) have proposed that Est-6 cisacting regulatory polymorphisms may be important contributors to adaptive variation (see also Oakeshott et al, 1994;. Odgers et al (1995) identified a nucleotide substitution responsible for the Rsa I polymorphism (T !…”
Section: Polymorphism At the Esterase-6 (Est-6 ) Locusmentioning
confidence: 99%
“…As in the current study, our parallel studies of juvenile fitness (juvenile survival and development time) in the same lines found no clear fitness associations for EST6 allozyme status but some strong associations for EST6 activity levels (Oakeshott et al, 1994). The physiological basis for the selection underlying the EST6-F/EST6-S allozyme clines therefore remains a mystery, while the evidence that EST6 activity levels are subject to selection is strengthened.…”
Section: Discussionmentioning
confidence: 61%
“…In all except one case, the various fitness components were tested on the same panel of lines; line 3 was lost before the tests of remating frequency were carried out, so line 11, of similar allozyme and activity status (Table 1), was measured for this variable instead. Media and other culture conditions were as in Oakeshott et al (1994).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation